Strategi Meningkatkan Efektifitas Penyaluran Dana Zakat di Masjid Jogokariyan Yogyakarta - Almustofa, Sodiq; Awal Amarudin, Amin (Indonesian Journal of Islamic Economics and Business, 2024)
As a developing country with the second largest Muslim population in the world, Indonesia certainly has great potential in developing zakat fund management, however, there are still many zakat fund management institutions that do not yet have a mature strategy for optimizing their management. Currently there is at least one institution. amil zakat company which is quite famous for its good management of zakat funds, namely Baitul Maal Jogokariyan Mosque (BMMJ). This research aims to examine how effective strategies have been implemented by BMMJ in managing zakat funds. This research uses a descriptive qualitative approach in its discussion, the results of this research show that BMMJ uses at least 4 approaches adopted from saters theory in optimizing its processing management.